2008
DOI: 10.1063/1.2833820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of monodisperse magnetite nanocubes

Abstract: Synthesis and magnetic properties of gold coated iron oxide nanoparticles J. Appl. Phys. 105, 07B504 (2009); 10.1063/1.3059607 Synthesis of self-assembled monodisperse 3 nm FePd nanoparticles: Phase transition, magnetic study, and surface effectThe monodisperse Fe 3 O 4 nanocubes with controllable sizes from 6.5 to 30.0 nm have been synthesized in one pot. The shape-induced texture of the self-assembled nanocube superlattices has been deposited onto substrates by a convective assembly technique. The cubelike s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
117
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 15 publications
2
117
1
5
Order By: Relevance
“…On the basis of the factors above, the Fe 3 O 4 particles exhibit high dielectric loss. [33,35,48]. For example, Olmedo et al [48] investigated the complex permittivity and complex permeability of ferromagnetic particles by the extending Bruggeman method, and found that nonspherical particles showed higher ″ and ″ compared with spherical magnetic particles.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…On the basis of the factors above, the Fe 3 O 4 particles exhibit high dielectric loss. [33,35,48]. For example, Olmedo et al [48] investigated the complex permittivity and complex permeability of ferromagnetic particles by the extending Bruggeman method, and found that nonspherical particles showed higher ″ and ″ compared with spherical magnetic particles.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, nonspherical Fe 3 O 4 has larger anisotropic energy compared with the spherical case [35]. The larger anisotropic energy can allow the magnetic resonance to shift to the high frequency region, and thereby improve the magnetic loss [6,10,11].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…FeCo alloy nanoparticles 27 and FePt alloy 28 were also produced through a similar synthetic procedure. Recently, Yang et al 29 used the similar method to synthesize monodisperse Fe 3 O 4 nanocubes. Hyeon's group employed the thermal decomposition of metal-surfactant complexes to synthesize monodisperse metal, 30,31 metal oxides, [32][33][34] and ferrite nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…The shape of the NPs depends on the preparation methods. Several studies have demonstrated the controllable synthesis of nonspherical iron oxide NPs with cubic [5,6], hexagonal [7], and rod [8][9][10] morphologies. It was shown that the size of spherical Fe 3 O 4 NPs prepared by hydrolysis can be in the range from 10 to 40 nm in mean diameter.…”
Section: Introductionmentioning
confidence: 99%